THE INFLUENCE OF THE LEADERSHIP, SATISFACTION AND COMMITMENT FOR EMPLOYEE SECRETARIAT OF PARLEMENT PERMORMANCE AT PASAMAN REGENCY - Fazril, Fazril (jurnal ekonomi, 2007)
Secretariat of Parlement of Regency Pasaman cause hthe often happened the communication as effect of implementation of officer mutation, wich functionary will bring its own leadership so that the mentioned can chang the spirit of officer job and change the satisfaction work the offer progressively, but there is also cause the satisfaction work and officer Performance become downhill. This research terget is to prove the leadership influence, satisfaction work and commitment to officer performance of secretariat of parlement of regency Pasaman. Method used with the double linier regression by object research is entire all officer of secretariat of parlement of regency Pasaman as much 43 people. Result of this research give the public information and picture foor the management that leadership, satisfaction work and commitment have the important meaning in improving officer performance. On that account management of secretariat of parlement of regency Pasaman so that  to be more paying attention and improving leadership, satisfaction work and commitment by improving.